Evidencia serológica de la infección por herpesvirus equino tipos 1 y 4 en dos regiones de Colombia - Ruiz Sáenz, Julián; Góez, Yenny; Urcuqui Inchima, Silvio; Góngora, Agustín; López Herrera, Albeiro (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Equine herpesviruses 1 and 4 (EHV-1 and EHV-4) are world wide spread viruses that cause significant economic losses. The primary infection of both viruses occurs in the upper respiratory tract, it can progress trough the mucose and can cause abortions in the last third of pregnancy, neonatal foal death, and non specific neurological syndromes. The EHV-1 is associated mainly whit abortion whereas EHV-4 is more related to respiratory disease. Infected animals rapidly overcome clinical symptoms but then remain infected rapidly overcome clinical symptoms but then remain infected infected all the life. In 2001 the first isolation of an EHV was reported in Colombia, but up-to-date, there are no up-to-date, there are no reports that confirm and determine the type of isolated virus. The aim of the resent work was to perform the type of isolated virus. The aim of the present work was to perform a serologic study in order to determine the presence of HVE-1 and HVE-4, in clinically healthy non- clinically healthy nonvaccinated horses. Serum samples n = 139 were drawn from healthy animals at two regions of Colombia erum samples n = 139 were drawn from healthy animals at two regions of Colombia drawn from healthy animals at two regions of Colombia two regions of Colombia (Antioquia and Meta department); an indirect ELISA test was performed to evaluate the presence of antibodies recognizihg to glycoprotein G of EHV-1 and EHV-4. We found that 98.7 and 96.6% of sera in Antioquia and Meta respectively were positive for EHV-4; the positivity for EHV-1 in Antioquia and Meta; the positivity for EHV-1 in Antioquia and Meta were 18.8 and 33.3% respectively. This is the first study that reports presence of antibodies to EHV-1 and 18.8 and 33.3% respectively. This is the first study that reports presence of antibodies to EHV-1 and EHV-4 in clinically healthy non-vaccinated horses in Colombia. These results suggest the establishment of the virus in the equine population of the studied regions and possibly in other areas of the country.